Association of GSDMD with microvascular-ischemia reperfusion injury after ST-elevation myocardial infarction - Sun, Wenjing; Wang, Chunqiu; Cui, Shihua; Wang, Yan; Zhao, Shenghui; Lu, Min; Yang, Fan; Dong, Shujuan; Chu, Yingjie (Frontiers in Cardiovascular Medicine, 2023)
Abstract Objectives Little is known about the clinical prognosis of gasdermin D (GSDMD) in patients with ST-elevation myocardial infarction (STEMI). The purpose of this study was to investigate the association of GSDMD with microvascular injury, infarction size (IS), left ventricular ejection fraction (LVEF), and major adverse cardiac events (MACEs), in STEMI patients with primary percutaneous coronary intervention (pPCI). Methods We retrospectively analyzed 120 prospectively enrolled STEMI patients (median age 53 years, 80% men) treated with pPCI between 2020 and 2021 who underwent serum GSDMD assessment and cardiac magnetic resonance (CMR) within 48 h post-reperfusion; CMR was also performed at one year follow-up. Results Microvascular obstruction was observed in 37 patients (31%). GSDMD concentrations ≧ median (13 ng/L) in patients were associated with a higher risk of microvascular obstruction and IMH (46% vs. 19%, P = 0.003; 31% vs. 13%, P = 0.02, respectively), as well as with a lower LVEF both in the acute phase after infarction (35% vs. 54%, P < 0.001) and in the chronic phase (42% vs. 56%, P < 0.001), larger IS in the acute (32% vs. 15%, P < 0.001) and in the chronic phases (26% vs.11%, P < 0.001), and larger left ventricular volumes (119 ± 20 vs 98 ± 14, P = 0.003) by CMR. Univariable and multivariable Cox regression analysis results showed that patients with GSDMD concentrations ≧ median (13 ng/L) had a higher incidence of MACE (P < 0.05). Conclusions High GSDMD concentrations in STEMI patients are associated with microvascular injury (including MVO and IMH), which is a powerful MACE predictor. Nevertheless, the therapeutic implications of this relation need further research.